2017
DOI: 10.3386/w23153
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Economic Impact of the H-1B Program on the U.S.

Abstract: for insightful comments and NE Barr for editorial assistance. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research.NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…The negative effect of domestic skill acquisition in the short run will, however, be small when the skill acquisition process is fairly short. And there is a possibility that for reasons such as social stigma, native managers will, in response to the arrival of migrant managers, seek to switch to science even in the absence of subsidies to do so (Bound et al 2017). This effect too is a dynamic consideration from which our model abstracts.…”
Section: Discussionmentioning
confidence: 99%
“…The negative effect of domestic skill acquisition in the short run will, however, be small when the skill acquisition process is fairly short. And there is a possibility that for reasons such as social stigma, native managers will, in response to the arrival of migrant managers, seek to switch to science even in the absence of subsidies to do so (Bound et al 2017). This effect too is a dynamic consideration from which our model abstracts.…”
Section: Discussionmentioning
confidence: 99%
“…o  Benefits: o A permit for one year at a time o After three years, entrepreneur can apply for a permanent residence permit o Entrepreneur's family members can apply for family immigration 16 https://www.mtep.my/ 17 https://business.gov.nl/coming-to-the-netherlands/permits-and-visa/startup-visa/ 18 https://www.newzealandnow.govt.nz/investing-in-nz/visas/entrepreneur-visa 19 https://www.udi.no/en/want-to-apply/work-immigration/skilled-workers/#link-831  Requirements: o Completion of a vocational training programme of at least three years at upper secondary school level, for example as a carpenter or health worker; there must be a corresponding vocational training programme in Norway, or o Completion of education or degree from a university/university college, for example a bachelor's degree as an engineer or nurse, or o Special qualifications that entrepreneur has obtained through long work experience, if relevant in combination with courses etc. (under exceptional circumstances) o Possess plans to engage in long-term business activities in Norway as a sole proprietorship o Plans to engage in business that requires the entrepreneurs' qualifications as a skilled worker o Likelihood that the business will generate a profit of at least NOK 246 246 per year pretax per an assessment conducted by the county authority o Possession of a permit from public authorities, if applicable…”
Section: Italy 13mentioning
confidence: 99%
“…However, both studies fail to identify the likely reasons for dependence on international students and talents: (i) cuts in US education budgets (Bound et al, 2016) which has forced universities to depend on international students and even multinationals for education finance and (ii) cuts in advanced placement classes at the pre-university levels, which short-changes many US students (Jackson et al, 2018;Hyman, 2017;Card and Payne, 2002). 15 Furthermore, although Bound et al (2017) found that H-1B visas lead to decline in wages in the US, a result disputed by other studies (Peri et al, 2015;Kerr et al, 2015), it was also found that the lack of preparation of the US students 16 , which results in poor quality, does matter (Richey and Rosburg, 2017;Bound et al 2010). School segregation and inequality of opportunities also aggravate the problem (Golden, 2006).…”
Section: (Iii) Consequences Of International Studentsmentioning
confidence: 99%